2009
DOI: 10.1007/s11999-009-0772-3
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Metal™ Cups for Acetabular Defects With 50% or Less Host Bone Contact

Abstract: Acetabular component revision in the context of large contained bone defects with less than 50% host bone contact traditionally have been treated with roof reinforcement or antiprotrusio cages. Trabecular Metal TM cups (Zimmer, Inc, Warsaw, IN) may offer a reasonable treatment alternative. We evaluated the clinical and radiographic outcome of this mode of treatment. We prospectively followed 53 hip revision acetabular arthroplasty procedures performed with Trabecular Metal TM cups for contained defects with 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 22 publications
(48 reference statements)
1
69
0
7
Order By: Relevance
“…Other authors have reported similar improvements in functional scores after revision hip surgery; Lakstein et al [18] reported a significant improvement to a postoperative Merle d'Aubigné-Postel score of 10.6 with the use of TM 1 cups for complex acetabular defects. In his pelvic discontinuity series treated with a distraction technique, Sporer et al [28] reported a significant increase in Merle d'Aubigné-Postel functional score from 3.3 to 9.6 after the revision surgery.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Other authors have reported similar improvements in functional scores after revision hip surgery; Lakstein et al [18] reported a significant improvement to a postoperative Merle d'Aubigné-Postel score of 10.6 with the use of TM 1 cups for complex acetabular defects. In his pelvic discontinuity series treated with a distraction technique, Sporer et al [28] reported a significant increase in Merle d'Aubigné-Postel functional score from 3.3 to 9.6 after the revision surgery.…”
Section: Discussionmentioning
confidence: 76%
“…Although this number might seem high, it is important to take into account that these cases are very complex procedures with several previous surgeries. The previously reported complication rate for complex acetabular revisions treated with TM 1 with or without augments ranges from 5% to 20% [1,7,17,18]. Additionally, in series treating pelvic discontinuities, the complication rate ranged from 16% to 29% [25,28,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations